2022
DOI: 10.3390/atmos13060943
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Bi-Polar Leader Inception and Propagation from Flying Aircraft Prior to a Lightning Strike

Abstract: Lightning is one of the major environmental threats to aircraft. The lightning strikes during flying are mostly attributed to aircraft-triggered lightning. The first step toward designing suitable protective measures against lightning is identifying the attachment locations. For this purpose, oversimplified approaches are currently employed, which do not represent the associated discharge phenomena. Therefore, in this work, a suitable model is developed for simulating the inception and propagation of bi-polar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Hence, in the present work an attempt has been made to quantify this vulnerability using a model for airplane-initiated bipolar leader discharges. [8] investigation. The exterior skin of the airplane model is segregated into 11,000 surface elements which are triangular in shape through the use of Mesh Lab software.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Hence, in the present work an attempt has been made to quantify this vulnerability using a model for airplane-initiated bipolar leader discharges. [8] investigation. The exterior skin of the airplane model is segregated into 11,000 surface elements which are triangular in shape through the use of Mesh Lab software.…”
Section: Introductionmentioning
confidence: 96%
“…Earlier investigations [8,11,12] have demonstrated that in the mode of lightning incepted by airplane, the potential initial attachment points are primarily limited to the extreme ends of the airplane, including the vertical fins, nose cone, wingtips, and similar areas. Apart from these, other extremities formed by the surface-mounted antennas are also present on the airplane.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations